UPAYA PENCEGAHAN DAN PENANGANAN PENYAKIT DEGENARTIF PADA LANJUT USIA - Nurul Hidayah; Esti Widiani; Lingling Marinda Palupi; Ira Rahmawati (Politeknik Kesehatan Kemenkes malang, 2022)
The elderly are a high-risk population for various degenerative diseases, including gout, hypertension, and diabetes mellitus. Lack of information and knowledge of the elderly about degenerative diseases, healthy lifestyles, and early prevention patterns are the main causes of the high incidence of disease complications in the elderly. The purpose of this community service activity, in general, is to improve the health status of the community through increasing the knowledge of the elderly about degenerative diseases and their prevention efforts in Sumberporon Village. The method of activities carried out in this activity is lecture and discussion. From the results of the counselling activities that have been carried out, it can be concluded that there is an increase in the knowledge of the elderly about gout, hypertension, hypercholesterolemia and diabetes mellitus in Sumberporong Village. In addition, the enthusiasm of the elderly in the discussion and question and answer sessions showed that the curiosity of the elderly about their health was quite high. Knowledge of these degenerative diseases is very necessary so that the elderly can independently maintain their health.